5. Millennial Sovereignty, Total Religion, and Total Politics - Moin, A. Azfar (History and theory, 2017)
Discussions of kingship and sovereignty in early modern India have struggled to fully comprehend and assess the work and life of Akbar (r. 1556–1605), the celebrated and most famous ruler of the Mughal Empire. The Mughal emperor's incomparable energy and imagination had lit up, like never before in the history of Islam, the vast networks and institutions of knowledge and practice that could be deployed in the service of sacred kingship. Rather than demonstrate a local history of Indic kingship, Akbar's intersections with networks and institutions show a history that stretched back centuries and linked South Asia to post-Mongol Iran and Central Asia, and were the crucibles in which a “millennial science” was cultivated. The implications for studying “millennial science” extend beyond the early modern world and into a consideration of sovereignty in modern South Asia.